(untitled) (KYAMC Journal, 2017)
Background: Cisplatin an old chemotherapeutic agent used to treat various types of cancers, including sarcomas, some carcinomas e.g. small cell lung cancer and ovarian cancer, lymphomas and germ cell tumors etc. Most important toxicity of cisplatin is nephrotoxicity produced by cisplatin itself and its few metabolites, which are some time fatal. Objectives: Present study was to determined the comparative study and the level of toxicities of cisplatin and their metabolires by using Brine Shrimp Lethality Bioassay. Methods: In this study, cisplatin and its four possible metabolites (CM2 to CM5) were isolated from the 24 hours collected urines of 5 cisplatin treated cancer patients using conventional chromatographic techniques as well as HPLC, were placed to comparative cytotoxic study using brine shrimp lethality bioassay. Results: Comparative to cisplatin, its metabolites are more toxic, specially CM2 (Meta 2, LC50=1.2?gm/ml) and CM3 (LC50=1.08 ?gm/ml), CM4 (Meta 4, LC50=1.182?gm/ml) which is correlate to the previous study (p<0.01*). Conclusion: Cisplatin can form monohydrated complexes by hydrolytic reactions. The monohydrated complex is more toxic to the renal cells than cisplatin but it is not kidney specific. KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 15-20